2006
DOI: 10.1097/01.fjc.0000211764.52012.e3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol on Endothelial Progenitor Cells and Their Contributions to Reendothelialization in Intima-injured Rats

Abstract: The aim of this study was to investigate the effects of resveratrol on endothelial progenitor cell (EPC) activities in vitro and on the mobilization of circulating EPCs, and reendothelialization in balloon-injured aorta of rats. After being isolated, cultured, and characterized, human EPCs were stimulated with resveratrol. We found that a low concentration of resveratrol (1 microM) led to significant enhanced activities of proliferation, migration, and adhesion, as well as promoting endothelial nitric acid syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 36 publications
3
23
1
Order By: Relevance
“…While Zu, et al reported SIRT1 promotes proliferation of primary porcine aortic ECs measured by crystal violet [21], our results showed that the down-regulation of rat aortic EC proliferation is induced when SIRT1 is activated by either NSS or resveratrol, which is an activator doubled the rate of deacetylation by SIRT1 at about 11 µM [37]. Resveratrol increased the proliferative, migratory, and adhesive activities of endothelial progenitor cells [38]. A recent study showed that resveratrol inhibited cell proliferation in a time- and dose-dependent manner in cultured human aortic and pulmonary arterial ECs [39].…”
Section: Discussionmentioning
confidence: 96%
“…While Zu, et al reported SIRT1 promotes proliferation of primary porcine aortic ECs measured by crystal violet [21], our results showed that the down-regulation of rat aortic EC proliferation is induced when SIRT1 is activated by either NSS or resveratrol, which is an activator doubled the rate of deacetylation by SIRT1 at about 11 µM [37]. Resveratrol increased the proliferative, migratory, and adhesive activities of endothelial progenitor cells [38]. A recent study showed that resveratrol inhibited cell proliferation in a time- and dose-dependent manner in cultured human aortic and pulmonary arterial ECs [39].…”
Section: Discussionmentioning
confidence: 96%
“…Resveratrol liquid formulations were prepared using ethanol (Sigma) as a solvent. Concentrations were chosen to reflect the range of doses previously shown to induce differential cellular effects 20 and all conditions were run in triplicate. The expression of SIRT1 was analysed by real-time-reverse transcription polymerase chain reaction (real time RT-PCR) (Applied Biosystems, Foster City, California).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding its cardioprotective role, NOS expression was shown to increase at 1 μM concentration while it was decreased at 60 nM (Gu et al, 2006). …”
Section: Administration Doses Routes and Bioavailability Of Resveramentioning
confidence: 99%